Super active surveillance for low-risk prostate cancer | Opinion: Yes - Leonardo Oliveira Reis; Danilo L. Andrade; Fernando J. Bianco (2019)
Prostate cancer is the most common solid tumor in men in western countries.Notwithstanding, its high incidence, most patients survive their prostate cancer diagnosis and die from other causes (1).This low cancer death event rate poses remarkable challenges for both patients and their treating physicians.Fundamentally the "overs", meaning overdiagnosis and overtreatment (2).Both particularly important as significant issues for patients arise as consequences of treatment.Distastefully, urinary incontinence and erectile dysfunction, among other, both exerting substantial impact in quality of life (3).This decade has witnessed results from three randomized trials.These robust studies clearly pointed to a limited benefit of definitive intervention such as surgery or radiation vs. surveillance modalities.The lack of differences in all cause survival and the relative low rate of metastasis 10 and 15 years after diagnosis have changed dramatically our knowledge on what is best to do when a man presents with a newly diagnosed prostate cancer (4-6).Not surprisingly, active surveillance (AS) has become a definitive alternative and common option.This strategy of management certainly decreased the morbidity rates associated to radical surgery or radiation (7).Specifically, AS is now a preferred option for many men with low-risk prostate cancer, gaining worldwide adoption due to robust data and is currently highlighted by many guidelines as the best treatment strategy for men with low risk (8,9).What constitutes the best approach to AS is an open question, as many protocols currently exists.However, to the patient selection questions, the field of urology sets the tone in low risk -PSA <10 ng/ml, WHO GG1 and a clinical stage T1c/T2a.There are several stricter protocols that have been developed and tested for AS.The Epstein criteria of ≤2 positive cores, <50% core involvement, and PSA density <0.15 ng/ml/cm³ carries 10 years rates of overall survival, cancer-specific survival, and metastasis-free survival of 94%, 99.9%, and 99.4%, respectively.Importantly, at 15 years, oncological outcomes such as metastasis-free survival and cancer specific survival change little (10).In Canada, specifically Klotz and collaborators have reported on single-arm cohorts of low--risk patients (Gleason score ≤6 and serum PSA level ≤10 ng/mL) and favorable intermediate-risk patients (serum PSA ≤15 ng/mL or a Gleason score of 7 [3+4]).The investigators reported 10-and 15-year metastasis-free survival rates of 96% and 95% vs 91% and 82% for low vs. intermediate